O processo de ensinar-aprender uma perspectiva crítica em psicologia escolar e educacional: histórias compartilhadas por uma supervisora e uma estagiária - Barbosa, Fabiana Marques (2013)
Through discussions held since the 1980s about Educational and School Psychology in a critical perspective, this research sought to understand the process of appropriation of this concept by a supervisor and an intern psychology of an Institution of Higher Education of Minas Gerais. Through the contributions of cultural-historical psychology, the methodological choice of this study was to know the professional education trajectory of participants, through investigative modality of oral history.. Each participant gave four sessions of interview, lasting 40 minutes on average. The analysis of this material enabled the construction of five categories: the mediation as an inherent process in professional choices and practical theoretical learning; challenges and contradictions as a fundamental part of the appropriation process of a critical perspective, suggesting that learning is developed dialectically; practical activity and theoretical studies as essential components in the process of learn concepts, this way the analysis pointed out the need to understand the theory and practice as a dialectically unit related to the learning process; and finally, the overseen internship as essential for the learning process of school psychology student. In this research, the internship indicates how the mediation between supervisor and intern was fundamental to the theoretical and practical appropriation of Educational and School Psychology in a critical perspective by the intern, as well as the importance of pedagogical actions of the supervisor in this process. The study points to the need for more research and actions for the school psychologist education in a critical perspective in order to consolidate this field with contextualized and emancipatory practices.